HUBUNGAN PAPARAN PESTISIDA DENGAN KEJADIAN MENOPAUSE DINI PADA PEREMPUAN PETANI DI DESA GIRIREJO KECAMATAN NGABLAK KABUPATEN MAGELANG - Zaedatul Farida; Onny Setiani; Nikie Astorina Yunita Dewanti (Jurnal Kesehatan Masyarakat (Undip), 2017)
Pesticides in farming play a role in improving the results of planting but on the other hand has a negative impact on health, causing exposure to population living in sorrounded area, including women. One of these can interfere the reproductive hormones in women. The aims of this study to determine association between peticides exposure and early menopause on women farmers in Girirejo village, Ngablak district, Magelang regency. This was an observational analytic study using cross sectional approach. Population in this study were women farmers aged 30-45 years and do not use hormonal contraceptives. The samples of 83 women farmers were taken using purposive sampling method. Data were analyzed using frequency distribution and Chi-Square test. The results of this study showed significant association between working period (p=0.001), working duration (p=0.025), method of pesticides storage (p=0,022), and completeness of using personal protective equipment (p=0,016) with early menopause incidence. While involvement in agriculture (p=0,289), spraying frequency (p=0,219), act of spraying on the wind direction (p=0,161), method of pesticides mixing (p=0,546), and personal hygiene (p=0,594) do not showed significant association with early menopause incidence. There were 31 women farmers who suffered early menopause. The average age of early menopause was 42.48 years. The Conclusions in this study were important to protect women from pesticides exposure in agriculture area because it may cause long term negative effects. Women farmers should decrease working duration, use pesticides properly and wisely, increase  the use of personal protective equipment to avoid pesticides exposure into the body.